Pengaruh Smart Card Anemia Pada Remaja Putri (REMATRI) di SMP Negeri 11 Jayapura - Isna Ainurrohimah; Selina Lestari; Nur Nabila; Rosa Simatauw; Murina Malyo; Ristina Rosauli Harianja (Poltekkes Kemenkes Jambi, 2025)
Background: Adolescent girls are at high risk of anemia due to significantly increased iron requirements, low iron intake, dietary habits, and higher-than-usual menstrual bleeding. Anemia in adolescent girls has significant consequences even after pregnancy, increasing the risk of maternal and neonatal mortality. The purpose of this study was to increase adolescent girls' knowledge of anemia prevention at SMP Negeri 11 Jayapura. Methods: This study used a quantitative approach with a One Group Pre-Post-Test-Design, namely by using a pre-post questionnaire instrument. The number of samples was 46 ninth-grade female students of SMP Negeri 11 Jayapura. The sampling technique used purposive sampling. Data analysis used univariate analysis and bivariate analysis using the paired sample T-test. Results: The results of the study showed that the results of the paired sample test showed that there was a difference in the average learning outcomes between the pre-test 65.65 < post-test 89.35, with a sig value (2-tailed) of 0.000 <0.05, so it can be concluded that there is an influence of extension activities in increasing the knowledge of female students of SMP Negeri 11 Jayapura. Conclusion: There is an influence of extension activities on increasing the knowledge of female students at SMP Negeri 11 Jayapura.